O serviço social e sua contribuição na melhoria da qualidade de vida das pessoas com deficiência - (:unkn) unknown (Universidade Federal do Pampa, 2011)
Among the challenges to guarantee rights to Disabled Persons in Brazil, it is included the search to be executed efficacious social policies that attend these subjects. From the motion that proposes the Social Inclusion of Persons with Disabilities there is the recognition that we all have characteristics that differ us and so need be though and materialized policies in the perspective to enable the rights that every person has to maintain their own characteristics before the society. Considering that studies and systematics about the subject People with Disabilities are relatively recent. This movement of valorization has been gaining social visibility recently, and it is understood as an expression of a social movement of the population excluded from society. This course conclusion work refers to the experiences obtained during the compulsory internship I and II at the neighborhood Passo's Reference Centre for Social Assistance. In the period 2010/2 and 2011/1 was developed the intervention project called "Social work in the perspective to contribute in the improving life quality of children with disabilities." This project had by general objective to develop activities to know the reality of Children with Disabilities, which are part of the scope of the CRAS Passo, to contribute in the preservation of the integrity and improving of the quality of life these users, in the perspective of the construction of inclusive actions. This study sought to contribute to the access of the children with disabilities' responsible for coexistence groups with the objective to strengthen the links between these children, their families and the society. It developed extensive actions such as: support, information, orientation and referral, through of groups of coexistence and exchange of experiences. At the end we made observations to contribute to the guarantee of the quality of life of the Children with Disabilities, making possible the exercise of citizenship and their inclusion in social life, these components are crucial for these individuals live in a way to search their emancipation and autonomy.
Keywords: Política social; Deficientes; Pessoas com deficiência; Social Policy; Disabled; CNPQ::CIENCIAS SOCIAIS APLICADAS